Do Elections Affect Immigration? Evidence From French Municipalities - Benoît Schmutz; Gregory Verdugo (Institute of Labor Economics (IZA), 2023)
Using thirty years of municipal elections in France, we show that election results affect the share of immigrants across municipalities. In municipalities where a left- instead of right-wing mayor has been elected, the share of immigrants in the population grows faster by 1.5 p.p. within six years after the elections, and by 3 p.p. within twelve years. To a large extent, these effects are driven by partisan differences in public housing constructions and changes in the composition of the population within existing public housing units. They also are associated with greater incumbency advantage, in line with a model of strategic partisan behavior.
Keywords: D72; H4; H7; R38; 330; local elections; public housing; immigration